Advanced Catalytic and Electrocatalytic Performances of Polydopamine‐Functionalized Reduced Graphene Oxide‐Palladium Nanocomposites. Issue 18 (31st August 2016) - Fu, Li; Lai, Guosong; Zhu, Deming; Jia, Baohua; Malherbe, Francois; Yu, Aimin
Abstract: A polydopamine‐functionalized reduced graphene oxide (PDA‐RGO)/Pd nanocomposite was synthesized by a simple wet chemical approach at room temperature. Graphene oxide (GO) was first modified with PDA by the self‐polymerization of dopamine (DA) followed by the deposition of Pd nanoparticles. UV/Vis and FTIR spectroscopies confirmed the reduction of GO to RGO during the self‐polymerization of DA. SEM images revealed that Pd nanoclusters were formed on both sides of the PDA‐RGO sheets. The as‐prepared PDA‐RGO/Pd nanocomposites exhibited excellent catalytic activity in the chemical degradation of methylene blue with a reaction rate constant of 0.6028 min −1, which was 2.5‐fold faster than that of the PDA/Pd catalyst without RGO. Moreover, the PDA‐RGO/Pd nanocomposite also showed an outstanding electrocatalytic activity towards the electro‐oxidation of paracetamol. The current response had a linear relationship to the concentration of paracetamol in the range of 0.28–100 μm with a low detection limit of 0.087 μm (S/N=3). In addition, the sensor also exhibited good selectivity for the detection of paracetamol. Abstract : Put palladium on it : An advanced catalyst based on polydopamine‐functionalized reduced graphene oxide (PDA‐RGO)/Pd nanocomposite is synthesized by a simple wet chemical approach at room temperature. Outstanding catalytic and electrocatalytic properties are observed for the catalytic degradation of methylene blue and the electrocatalytic determination of paracetamol, respectively.